2020
DOI: 10.1038/s41556-020-0575-z
|View full text |Cite|
|
Sign up to set email alerts
|

PD-L1-mediated gasdermin C expression switches apoptosis to pyroptosis in cancer cells and facilitates tumour necrosis

Abstract: Pyroptosis is critical for macrophages against pathogen infection, but its role and mechanism in cancer cells remain unclear. PD-L1 has been detected in the nucleus with unknown function. Here, we show that PD-L1 switches TNFα-induced apoptosis to pyroptosis in cancer cells, resulting in tumor necrosis. Under hypoxia, p-Stat3 physically interacts with PD-L1 and facilitates its nuclear translocation, enhancing gasdermin C (GSDMC) gene transcription. GSDMC is specifically cleaved by caspase-8 with TNFα treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
523
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 651 publications
(597 citation statements)
references
References 54 publications
5
523
0
Order By: Relevance
“…Similar to other GSDMs, the N-terminal domain of GSDMC (GSDMC-NT) was able to induce pyroptosis in human 293T cells ( Ding et al, 2016 ). Recently, Hou et al (2020) revealed that GSDMC could be specifically cleaved by caspase-8, switching TNF-α-induced apoptosis to pyroptosis in breast cancer cells. They found that caspase-6 could also activate GSDMC.…”
Section: The Biological Characteristics Of Gasderminsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other GSDMs, the N-terminal domain of GSDMC (GSDMC-NT) was able to induce pyroptosis in human 293T cells ( Ding et al, 2016 ). Recently, Hou et al (2020) revealed that GSDMC could be specifically cleaved by caspase-8, switching TNF-α-induced apoptosis to pyroptosis in breast cancer cells. They found that caspase-6 could also activate GSDMC.…”
Section: The Biological Characteristics Of Gasderminsmentioning
confidence: 99%
“…STAT3 could be activated by phosphorylation at Tyr 705 (STAT3-Y705) in response to hypoxia ( Pawlus et al, 2014 ). Under hypoxia, STAT3-Y705 interacted with the important immune-checkpoint programmed death-ligand 1 (PD-L1) and favored its nuclear translocation, hence enhancing GSDMC transcription ( Hou et al, 2020 ). GSDMC was then cleaved by caspase-8 in breast cancer cells treated with TNF-α.…”
Section: The Role Of Gasdermins In Cancer Pathogenesismentioning
confidence: 99%
“…Hence, like GSDMD, other GSDM members have been expected to execute pyroptotic cell death after being processed by proteases at the linker region. Indeed, recent studies have shown that proteolytic activation of GSDME, GSDMB, and GSDMC by certain caspases and granzymes can lead to necrotic cell death ( Figure 2 ) [ 25 , 26 , 27 , 28 , 29 , 30 ]. The Nomenclature Committee on Cell Death has proposed to define pyroptosis as depends on the formation of plasma membrane pores by members of the GSDM family, often (but not always) as a consequence of inflammatory caspase activation [ 1 ].…”
Section: Gsdm Family Proteinsmentioning
confidence: 99%
“…Given the pro-inflammatory properties of regulated necrosis, it is worth considering whether non-apoptotic cell death pathways described recently are involved in traditional ICD induction. Of note, in a recent study, GSDMC-dependent pyroptosis occurred in cancer cells after treatment with anthracyclines, such as doxorubicin and epirubicin that are well-known ICD inducers, but not with most other chemotherapy drugs tested [ 29 ]. These anthracyclines induced the expression of GSDMC and activation of caspase-8 simultaneously, resulting in proteolytic activation of GSDMC by caspase-8, whereas most other drugs only induced GSDMC expression.…”
Section: Pyroptosis and Antitumor Immunitymentioning
confidence: 99%
See 1 more Smart Citation